2020
DOI: 10.1108/oir-08-2020-0386
|View full text |Cite
|
Sign up to set email alerts
|

The presumed influence of digital misinformation: examining US public’s support for governmental restrictions versus corrective action in the COVID-19 pandemic

Abstract: PurposeInformed by the third-person effects (TPE) theory, this study aims to analyze restrictive versus corrective actions in response to the perceived TPE of misinformation on social media in the USA.Design/methodology/approachThe authors conducted an online survey among 1,793 adults in the USA in early April. All participants were randomly enrolled in this research through a professional survey company. The structural equation modeling via Amos 20 was adopted for hypothesis testing.FindingsResults indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 62 publications
2
49
0
Order By: Relevance
“…However, a few studies reported that misinformation led to fear and panic and to people becoming tired of hearing about COVID-19. There is evidence that misinformation can evoke negative emotions, 34 which could, in turn, further contribute to its spread. 35…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies reported that misinformation led to fear and panic and to people becoming tired of hearing about COVID-19. There is evidence that misinformation can evoke negative emotions, 34 which could, in turn, further contribute to its spread. 35…”
Section: Discussionmentioning
confidence: 99%
“…Without preexisting immunity to this novel coronavirus, it is believed that everyone is susceptible to COVID-19; however, it has been often compared to the flu, and the danger of COVID-19 has been downplayed by some American media and politicians. Such misinformation could have an impact on the public’s belief in the threat of this disease [ 16 ]. Based on previous findings of age disparity in risk perception, we hypothesize that older age is associated with higher perceived severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a national strategy for battling the pandemic also leaves state and local governments responsible for creating their own response strategies and policies [ 1 ]. However, misinformation and disinformation continue to circulate on social media platforms with unprecedented volume and velocity, which affects the public’s trust in and response to governmental restrictions and corrective actions [ 2 , 3 ]. Thus, it is crucial to examine how state and local health departments communicate with their stakeholders on social media platforms.…”
Section: Introductionmentioning
confidence: 99%